On H-Irregularity Strengths of Square Chain Graphs - Faisal Susanto (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2026)
This paper investigates three types of graph labeling schemes, namely H-irregular vertex, edge, and total labeling. These labeling frameworks are examined in the context of square chain graphs SCn for n>=1. Furthermore, by establishing matching lower and upper bounds, the exact values of the vertex, edge, and total SCm-irregularity strengths of SCn are determined for all m with 1<=m<=n.